A case study on the phenomenon of "ginsangkayan" in Hernani, Eastern Samar - Loste, Salvacion C. (2004)
Phenomenon of "ginsangkayan" was investigated. Three groups of respondents with ten respondents each group from "ginsangkayan", parent and peer participated in order to find out the extent of the effect of persons "nga dire sugad ha aton," the common behaviors manifested of "ginsangkayan" and the effect of the healing power of "tambalan" and holy objects upon "ginsangkayan". They disclosed that "digkosanon" has great effect upon "ginsangkayan". They possess power to manipulate human beings. "Ginsangkayan" manifested similar behaviors before, during and after "digkosanons'" presence. They also accepted that "tambalan" and holy objects have healing effects upon "ginsangkayan".